STRATEGI PEMASARAN DIGITAL AYAM GEPREK WARBOX DI KABUPATEN KOLAKA - Adi, Yudistira; Sukotjo, Endro; Hamid, Nisrina (Mega Aktiva, 2025)
The rapid development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to optimize digital marketing strategies to enhance their business competitiveness. This study aims to analyze the implementation of digital marketing strategies and identify the challenges and obstacles encountered by Ayam Geprek Warbox in Kolaka Regency. This study employed a qualitative approach with a descriptive research design. The research informant was the owner of Ayam Geprek Warbox, who was purposively selected due to direct involvement in all digital marketing activities. Data were collected through in-depth interviews and documentation and analyzed using the Miles and Huberman interactive model, consisting of data collection, data reduction, data display, and conclusion drawing. The findings indicate that Warbox has implemented digital marketing by utilizing social media platforms such as WhatsApp, Facebook, and Instagram, which are aligned with the characteristics of local consumers, enabling effective and low-cost communication. However, the implementation remains constrained by unstructured and inconsistent content creation, low customer engagement, limited human resources with digital marketing competencies, and the absence of data-driven performance evaluation. The study concludes that digital marketing has contributed positively to the business development of Warbox. Nevertheless, optimizing its effectiveness requires strengthening human resource capabilities, developing more structured content planning, increasing customer engagement, and implementing analytics-based evaluation to support more effective digital marketing strategies.ABSTRAK Perkembangan teknologi digital telah mendorong pelaku Usaha Mikro, Kecil, dan Menengah (UMKM) untuk mengoptimalkan strategi pemasaran digital sebagai upaya meningkatkan daya saing usaha. Penelitian ini bertujuan untuk menganalisis implementasi strategi pemasaran digital serta mengidentifikasi hambatan dan tantangan yang dihadapi Ayam Geprek Warbox di Kabupaten Kolaka. Penelitian menggunakan pendekatan kualitatif dengan desain deskriptif. Informan penelitian adalah pemilik Ayam Geprek Warbox yang dipilih secara purposive karena berperan langsung dalam seluruh aktivitas pemasaran digital. Pengumpulan data dilakukan melalui wawancara mendalam dan dokumentasi, sedangkan analisis data menggunakan model Miles dan Huberman yang meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi pemasaran digital Warbox telah memanfaatkan platform media sosial seperti WhatsApp, Facebook, dan Instagram yang disesuaikan dengan karakteristik konsumen lokal sehingga mampu menciptakan komunikasi yang efektif dan berbiaya rendah. Namun, implementasinya masih menghadapi berbagai kendala, seperti konten pemasaran yang belum terencana dan konsisten, rendahnya interaksi pelanggan, keterbatasan sumber daya manusia yang menguasai digital marketing, serta belum diterapkannya evaluasi berbasis data. Penelitian ini menyimpulkan bahwa pemasaran digital telah memberikan kontribusi terhadap pengembangan usaha Warbox, tetapi optimalisasi strategi memerlukan peningkatan kompetensi sumber daya manusia, penyusunan konten yang lebih terstruktur, peningkatan engagement pelanggan, serta penerapan evaluasi berbasis analitik untuk meningkatkan efektivitas pemasaran digital.